Trends and patterns in blended learning research (1965-2022) - Tonbuloglu, Betul; Tonbuloglu, Ismail (SPRINGER, 2023)
Blended learning (BL) applications, which are defined as a combination of online and face-to-face education processes and created with the strongest aspects of various teaching approaches, have attracted increasing attention particularly in recent years with the effect of the pandemic. Although blended learning studies, which have a wide range of content and variety of applications in the literature, have been examined by content analysis in many scientific studies, bibliometric studies that provide a comprehensive review of studies on BL and reveal a general map of scientific studies are extremely limited. The purpose of this research is to conduct a systematic analysis of BL studies around the world and to reveal general research trends by bibliometric method. In the scope of the research, 4,059 publications searched in the Scopus database between the years 1965-2022 were analyzed by VOSviewer and Leximancer software; the publications were examined from aspects such as year, subject, fund, citation, journal, country, common word, etc. An analysis of the research results reveals that studies on BL have increased in number in the literature since 2006; it has been found that the fields of social sciences, computer, medicine and engineering come to the forefront in the categorization of publications by subject, and the USA, UK, China and Australia are the most cited countries. As revealed by the findings of common word analysis, the studies mostly focus on the use of technology during the pandemic, current trends in education and technology, online learning environment and learner characteristics, teaching approaches, social media, motivation and medical education. Furthermore, it is understood that the most common terms in abstracts-keywords and titles of the studies reflect the learning process, the learner, the classroom environment, the model adopted, the system designed and medical education.
Keywords: Blended learning; Hybrid education; Flipped learning; Bibliometrics; Citation analysis; Common word analysis; BIBLIOMETRIC ANALYSIS; HIGHER-EDUCATION; TECHNOLOGY; SCOPUS; OUTPUT; Education & Educational Research